Narrative Tools and Strategies: Representation of Trauma in Bista’s The Andhi Khola - Sushil Ghimire, (Journal of Balkumari College, 2023)
This article explores the post-traumatic journey of the central character Gangi in the story The Andhi Khola by Daulat Bikram Bista. The aim of this study is to analyze Gangi’s journey and investigate the deep effects of trauma on her psyche and experiences. The methodology is a close reading and textual analysis of Bista’s work, examining key passages and themes related to Gangi’s trauma. Through this analysis, the article uncovers the emotional trajectory of Gangi, highlighting themes of loss, separation, and longing, as well as the continuing impact of trauma on her sense of self and her hope for her lover’s return. The findings of this study contribute to a deeper understanding of the transformative power of trauma and promote empathy for individuals who carry its burden. By revealing Gangi’s narrative, this research highlights the need for sensitivity and support in addressing the psychological effects of trauma in individuals’ lives.